Technical, Allocative, and Economic Efficiency of Rice Farming Using Data Envelopment Analysis (Dea) in Gantar District, Indramayu Regency - Alim, Alfan Naufal; Syah, Firman Hanafi Alam; Putra, Nanda Dwi; Aisyah, Siti (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study analyzes the technical, allocative, and economic efficiency of rice farming in Gantar District, Indramayu Regency, using Data Envelopment Analysis (DEA) with an input-oriented Variable Returns to Scale (VRS) model and Tobit regression to assess socioeconomic determinants of technical efficiency. Based on 99 rice farmers selected using the Slovin formula, results show an average technical efficiency of 0.974, indicating near-frontier performance, though labor input exhibits notable slack. Allocative efficiency averages 0.875, while economic efficiency reaches 0.829, implying a potential improvement of 17.1%. Tobit results indicate that education, experience, land status, group membership, and credit access do not significantly affect technical efficiency. The study underscores the need for better input optimization and cost management to improve farm efficiency and sustainability.